2019
DOI: 10.1093/bioinformatics/btz867
|View full text |Cite
|
Sign up to set email alerts
|

CRISPRitz: rapid, high-throughput and variant-aware in silico off-target site identification for CRISPR genome editing

Abstract: Motivation Clustered regularly interspaced short palindromic repeats (CRISPR) technologies allow for facile genomic modification in a site-specific manner. A key step in this process is the in silico design of single guide RNAs to efficiently and specifically target a site of interest. To this end, it is necessary to enumerate all potential off-target sites within a given genome that could be inadvertently altered by nuclease-mediated cleavage. Currently available software for this task is li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
41
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 38 publications
0
41
0
Order By: Relevance
“…There are multiple in silico tools available for predicting putative off-target sites. The recently developed CRISPRitz platform is the only bioinformatics tool that simultaneously accounts for mismatches, bulges, and genetic variants while distinguishing between coding and noncoding off-target sites [ 48 ]. However, in silico CRISPR design tools cannot replace the need for additional validation of off-target gene editing using targeted deep sequencing or, ideally, whole-genome sequencing to accurately quantify the Cas9 specificity.…”
Section: Gene-editing Toolsmentioning
confidence: 99%
“…There are multiple in silico tools available for predicting putative off-target sites. The recently developed CRISPRitz platform is the only bioinformatics tool that simultaneously accounts for mismatches, bulges, and genetic variants while distinguishing between coding and noncoding off-target sites [ 48 ]. However, in silico CRISPR design tools cannot replace the need for additional validation of off-target gene editing using targeted deep sequencing or, ideally, whole-genome sequencing to accurately quantify the Cas9 specificity.…”
Section: Gene-editing Toolsmentioning
confidence: 99%
“…Filtering based on features such as: GC content, presence of TTTT, gRNA secondary structure [18] sgRNA Scorer 2.0 Scoring using machine learning model, trained on [6] [7] CHOPCHOP Flag indicating position 20 containing guanine [17] A B (3,5,12,20) s (1,9,16,20) s (1,2,8,9) s (1,2,3,4) s (1,2,19,20)…”
Section: Toolmentioning
confidence: 99%
“…Other tools such as CRISPRseek [21], CasOT [20] and CRISPRitz [4] exist. However, we do not consider them here as already published results show that they perform poorly compared to others which we have included [11,4].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have showed that considerable variation is present across human populations and individuals contain large scale variations such as duplications not present in the reference [15]. The issue of individual specific genomic variations has been addressed in tools that are capable of designing personalized sgRNAs, namely AlleleAnalyzer [16], CrisFlash [17] and CRISPRitz [18] while Sun et al presented a tool to design sgRNAs for non-reference plant genomes [19]. However, these tools use reference genomes and sequencing reads to detect variations and may lack specificity if the individual contains duplications or regions missing from the reference.…”
Section: Introductionmentioning
confidence: 99%